2023
DOI: 10.1021/acsami.3c06015
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive and Highly Stretchable Piezoresistive Polymer Nanocomposites via Oxidative Chemical Vapor Deposition

Abstract: Electrically conductive polymer nanocomposites have been the subject of intense research due to their promising potential as piezoresistive biomedical sensors, leveraging their flexibility and biocompatibility. Although intrinsically conductive polymers such as polypyrrole (PPy) and polyaniline have emerged as lucrative candidates, they are extremely limited in their processability by conventional solution-based approaches. In this work, ultrathin nanostructured coatings of doped PPy are realized on polyuretha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The peak at 795 cm –1 is due to the characteristic absorption peak of α–α-linked pyrroles. , When comparing PPF and PPFP, it can be observed that PPFP initially undergoes less mass degradation at 100 °C. This is because the chloride dopants and volatile small molecules derived from the short-chain PPy oligomers evaporate during the heating process . As the temperature rises, the carbonyl groups in PPF begin to break down, leading to a rapid deterioration in the quality of the PPF fibrous membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 795 cm –1 is due to the characteristic absorption peak of α–α-linked pyrroles. , When comparing PPF and PPFP, it can be observed that PPFP initially undergoes less mass degradation at 100 °C. This is because the chloride dopants and volatile small molecules derived from the short-chain PPy oligomers evaporate during the heating process . As the temperature rises, the carbonyl groups in PPF begin to break down, leading to a rapid deterioration in the quality of the PPF fibrous membrane.…”
Section: Resultsmentioning
confidence: 99%
“…Silicon nanowires (SiNWs) and conductive polymers are frequently employed as piezoresistive materials. These sensors are known for their precision in static force measurements and compatibility with microfabrication techniques, making them ideal for integrating into wearable and implantable devices [202,203]. Both sensing mechanisms have been effectively applied in the design of bioelectronic devices to measure forces that are relatively small, yet critical for understanding physiological conditions.…”
Section: Force Sensingmentioning
confidence: 99%
“…Composite materials are formed by combining two or more materials with different chemical or physical properties to create a new material with distinct physical or chemical characteristics. With the advancement of modern technology, composite materials have been widely applied in various important and innovative industries both domestically and internationally, such as bio-composite materials [1], aerospace, maritime transportation, mechanical structural materials [2], and civil engineering [3][4][5]. Recent studies have shown that composite materials are widely used in automotive, underwater, and structural applications.…”
Section: Introductionmentioning
confidence: 99%